Sun Drying of Anchoviella on Racks - Prabhu, P.V.; Kandoran, M.K. (Fishery Technology, 2025)
Anchoveilla was dried on rack, cement floor and black surface. The fish was kept over these surfaces on trays of 1 x 0,5 m size. Though the initial drying was higher on the top deck of the rack, all the samples attained almost uniform moisture by 9 h drying. The dried fish had good colour and appearance. During storage, the white colour faded to yellow and then to brown. All the samples became slightly rancid by 22 weeks and highly rancid by 44 weeks